Peran Guru Tahfidz dalam Menguatkan Hafalan Santri di Pondok Pesantren Depok - Aqila Fikhia; Munakhiroh El Hajar (AZKIA: Journal of Islamic Education in Asia, 2025)
This study is based on the importance of tahfidz teachers in strengthening students' memorization. Al-Hidayah Islamic Boarding School has implemented a tahfidz program as an effort to form students who have a love for the Qur'an and have noble morals. However, there are challenges in maintaining consistency in memorization, especially because of laziness in students, differences in student abilities, and learning methods in memorizing. The purpose of this study is to find out about the role of tahfidz teachers in strengthening memorization and the obstacles and solutions of tahfidz teachers in strengthening students' memorization. The approach used in this study is a qualitative approach. The basis of this study was obtained through interviews, observations and documentation. The data collected were analyzed and presented in descriptive form. The data sources in this study were various evidence or facts collected for a specific purpose. Based on the source, research data can be divided into two types, namely primary data and secondary data. The results of the study indicate that the role of tahfidz teachers at Al-Hidayah Islamic Boarding School in strengthening memorization includes: teachers as educators, instructors, mentors, motivators, learning resources, elevators and innovators. This study also found several obstacles in the memorization process, such as lack of understanding of tajwid, limited time, differences in student abilities, and laziness. To overcome these obstacles, teachers provide solutions in the form of providing tajwid materials routinely, providing additional time outside the official schedule, implementing punishment for students who are alpha, and guiding students to continue to do murojaah gradually.